Author Correction: Morphological and immunohistochemical phenotype of TCs in the intestinal bulb of Grass carp and their potential role in intestinal immunity - Hanan H. Abd-Elhafeez (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.